2012
DOI: 10.3386/w17725
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Firm Factors in Demand, Cost, and Export Market Selection for Chinese Footwear Producers

Abstract: NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 23 publications
(46 reference statements)
1
14
0
1
Order By: Relevance
“…To explain the data we need firm and market specific demand shocks, as postulated here. Such demand shocks do much of the work in fitting the data, which is also consistent with the work of Roberts et al (2012) and Eaton et al (2011a,).…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…To explain the data we need firm and market specific demand shocks, as postulated here. Such demand shocks do much of the work in fitting the data, which is also consistent with the work of Roberts et al (2012) and Eaton et al (2011a,).…”
Section: Introductionsupporting
confidence: 70%
“…R BD,US and R US are approximated by the total Bangladeshi 41 Among other papers that emphasize the dominant role of changes in demand over productivity shocks are Roberts et al (2012), who show that demand shocks are the driving force behind firms' turnover, and Eaton et al (2011b), who demonstrate that changes in demand explain more than 80% of the drop in trade/GDP during the Great Recession of 2008-2009. 42 In previous work, see Demidova et al (2012), we showed that when the EU offered EBA preferences to Bangladesh, ROOs were less restrictive in non-wovens than in wovens.…”
Section: Policy Experimentsmentioning
confidence: 99%
“…Empirical studies in international trade such as Roberts et al . [] and Khandelwal et al . [] have demonstrated trade liberalization often confers additional efficiency gains through the channel of market share reallocation across individual exporters (i.e., exporting countries in the present case).…”
Section: Welfare Analysis Of the Coffee Cartelmentioning
confidence: 99%
“…(), Roberts et al. (), and Pozzi and Schivardi (). These intuitive approaches, however, are not feasible if price data are not observable to the researcher, which is quite common in production data sets.…”
Section: Introductionmentioning
confidence: 99%